Bax, Bcl-2, Fas and Fas-L antigen expression in human seminoma: correlation with the apoptotic index - Grobholz, Rainer; Zentgraf, Hanswalter; Köhrmann, Kai-Uwe; Bleyl, Uwe (Acta pathologica, microbiologica et immunologica Scandinavica, 2003)
Apoptosis plays a crucial role in the regulation of spermatogenesis in male germ cells and is, at least in part, modulated by Bcl-2, Bax, and the Fas pathway. Seminomas have a favourable outcome and respond to radio-/chemotherapy with an increased rate of apoptosis. The expression of Bax, Bcl-2, Fas and Fas-ligand (Fas-L) in human seminoma was evaluated and correlated with the apoptotic index. Twenty-nine classical seminomas were examined by immunohistochemistry and Western blotting using antibodies against Bax, Bcl-2, Fas and Fas-L. Apoptosis was detected by in-situ end-labeling of fragmented DNA and the apoptotic index (AI) was determined. Expression of Fas was found in 26 (89.7%) of Fas-L in 24 seminomas (82.2%); none of the tumours expressed Bcl-2. No correlation between the AI and Fas, Fas-L or Bcl-2 expression was found. Bax was demonstrated in 20/29 tumours (69%). Bax-positive tumours showed an increased AI of 4.75±2.38% in contrast to 2.60±1.23% of the Bax-negative tumours (P=0.002). The number of Bax-positive tumour cells and apoptotic cells revealed a significant correlation using χ2-test (P=0.04) and linear regression (r=0.54, P=0.001). Therefore, Bax seems to play a determinant role in the modulation of apoptosis in human seminoma that may be linked to a favourable outcome.